Psychosocial factors in patients with kidney failure and role for social worker: A secondary data audit. Issue 2 (8th May 2022) - Hansen, Micaella Sotera; Tesfaye, Wubshet; Sud, Kamal; Sewlal, Beena; Mehta, Bharati; Kairaitis, Lukas; Tarafdar, Surjit; Chau, Katrina; Razi Zaidi, Syed Tabish; Castelino, Ronald
Abstract: Background: People with kidney failure face a multitude of psychosocial stressors that affect disease trajectory and health outcomes. Objectives: To investigate psychosocial factors affecting people with kidney failure before or at start of kidney replacement therapy (KRT) and kidney supportive and palliative care (KSPC) phases of illness and to explore role of social worker during the illness trajectory. Methods: We conducted a secondary data audit of patients either before or at start of KRT (Phase 1) and at the KSPC (Phase 2) of illness and had psychosocial assessments between March 2012 and March 2020 in an Australian setting. Results: Seventy‐nine individuals, aged 70 ± 12 years, had at least two psychosocial assessments, one in each of the two phases of illness. The median time between social worker evaluations in Phase 1 and Phase 2 was 522 (116−943) days. Adjustment to illness and treatment (90%) was the most prevalent psychosocial issue identified in Phase 1, which declined to 39% in Phase 2. Need for aged care assistance (7.6%−63%; p  < 0.001) and carer support (7.6%−42%; p  < 0.001) increased significantly from Phase 1 to Phase 2. There was a significant increase in psychosocial interventions by the social worker in Phase 2, including supportive counselling (53%−73%; p  < 0.05), provision of education and information (43%−65%; p  < 0.01), and referrals (28%−62%; p  < 0.01). Conclusion: Adults nearing or at the start of KRT experience immense psychosocial burden and adaptive demands that recognisably change during the course of illness. The positive role played by the nephrology social worker warrants further investigation.